Effects of regional infrastructure and offered services in the supply chains performance: case ciudad juarez (2014)
In this paper appears an analysis of the effects of regional infrastructure and the services in the supply chains performance in manufacturing companies collated in Ciudad Juarez, Chihuahua, Mexico. To collect the information, 120 surveys were applied to companies, and to obtain a causal with structural equation modelling to explain those effects, a methodology of partial least squares was used with WarpPls 3.0®. The results indicate that a good level in the regional infrastructure has a positive impact on logistics services, and as a consequence in the costs. Also, the regional infrastructure has a positive impact on time delivery of products. Regarding the level of infrastructure (transport, telecommunications, and internet) and services (air, land, financial, legal) in Ciudad Juarez, respondents are considering that it is good, so the product deliveries are complete on time in the past 3 years.